ApoE Polymorphism Is Associated With C-Reactive Protein in Low-HDL Family Members and in Normolipidemic Subjects - Juhani Kahri; Aino Soro-Paavonen; Christian Ehnholm; Marja-Riitta Taskinen (Hindawi Limited, 2006)
The study was aimed to compare inflammatory parameters between carriers of apoE4 isoforms (apoE4/3, apoE4/2, and apoE4/4 phenotypes) and those of carrying apoE3 isoform without apoE4 isoform (apoE3/3 phenotypes and apoE2/3 phenotypes). The concentrations of serum hsCRP, sVCAM-1, sICAM-1, and sE-selectin were measured in 211 subjects from Finnish low-HDL families and in 157 normolipidemic subjects. The subjects with apoE4 isoform had lower concentrations of serum hsCRP both in low-HDL family members (p<0.05) and in normolipidemic subjects (p<0.01). The differences in serum CRP values remained significant after adjustment for age, BMI, smoking status, hypertension, gender, lipoprotein variables, and family number. We conclude that apoE phenotype has a strong influence on serum CRP values.